Advanced Combined Multi-Criteria Decision-Making Methodology with IndetermSoft Set for Comprehensive Analysis of Blended Physical Education Teaching in Colleges Framework - Xueda Yang (Neutrosophic Sets and Systems)
Prioritizing and weighing criteria is a crucial step in the decision-making process for many qualities. The stepwise weight assessment ratio analysis (SWARA) is the most often used multi-criteria decision-making (MCDM) weighting methods. The SWARA approach is the most effective way to evaluate criteria when policies are at the center of decision-making. Expert consultation is used to prioritize the criteria in the first phase, and the weighing procedure is the second crucial step. By adding the reliability assessment of experts' ideas as the first stage, this study aims to use SWARA method to compute the criteria weights of Blended Physical Education Teaching in Colleges. Then we use the root assessment method (RAM) to rank the alternatives. IndetermSoft set is used in this study to deal with indeterminacy and uncertainty in the values of the criteria. This study uses five criteria and ten alternatives to be evaluated.